Comparison of in vitro, in vivo, and in silico bioavailability results of different prednisone tablet formulations to assess the feasibility of possible biowaiver - Leonardo Henrique Toehwé; Thiago da Silva Honorio; Luiz Claudio Rodrigues Pereira da Silva; Thalita Martins da Silva; Luciana da Rocha Pitta; Livia Deris Prado; Lucio Mendes Cabral; Helvécio Vinícius Antunes Rocha (Ars Pharmaceutica, 2021)
Abstract Introduction: The immediate-release solid oral products containing very soluble and permeable drugs are candidates for the biowaiver process. This work aims to compare in vitro, in silico, and in vivo data to establish if previously published prednisone oral tablet formulations are biowaiver candidates. Method: To achieve this goal, permeation studies were conducted on Caco-2 cells. A previous bioequivalence study between the test and the reference drug product was applied on an in silico evaluation using Gastroplus® to assess the bioequivalence of two other previously proposed formulations. Results: The apparent permeability coefficient for prednisone presented a value of 3.69 x 10-5 cm/s in 180 minutes. The bioequivalence study shows that the tested and reference product was equivalent. The in silico simulations successfully predicted the pharmacokinetics of the tested and the other two formulations since they were validated with the in vivo study. Both exhibit the same plasma concentration vs. time profiles. Conclusions: Through the in silico results, it is possible to infer that the other two formulations tested may be bioequivalent concerning the reference product. This result may be helpful in biowaiver requesting. Toward to reduce costs and the use of human beings in bioequivalence studies, this approach could be an essential way to work in the pharmaceutical industry.